Excellent survival after R‐Hyper‐CVAD in hospitalized patients with high‐risk large B‐cell lymphoma: The Karolinska experience. Issue 4 (28th September 2021) - Sonnevi, Kristina; Ljungqvist, Maria; Jóelsson, Jóel Kristinn; Harrysson, Sara; Wästerlid, Tove; Bernell, Per; Wahlin, Björn Engelbrekt
Abstract: Patients with high‐risk aggressive B‐cell lymphoma exhibit poor survival after R‐CHOP. More intensive regimens yield higher rates of remission but also of complication. We investigated all 401 patients < 70 years with high‐risk (age‐adjusted [aa] international prognostic index [IPI] ≥2, extranodal, or bulky) aggressive B‐cell lymphoma hospitalized at Karolinska for urgent start of immunochemotherapy (129 R‐Hyper‐CVAD; 261 R‐CHOP/R‐CHOEP). Patients showed IPI 3–5 (70%), WHO PS ≥2 (49%), bulky disease (70%), extranodal (75%) and CNS (8%) involvement. Five‐year overall/progression‐free survival (OS/PFS) was better in patients who started R‐Hyper‐CVAD (84%/77%) compared with R‐CHOP/R‐CHOEP (66%/55%). Differences were independent in multivariable analysis, seen in all patient categories, and accentuated in extreme high‐risk disease: R‐Hyper‐CVAD vs. R‐CHOP/R‐CHOEP showed 5‐year PFS 69% vs.40% in aaIPI 3 and 88% vs. 38% in CNS involvement. For validation, survival was compared between the two Karolinska sites and calendar periods. Survival was superior 2006–2010 at the site that introduced R‐Hyper‐CVAD/R‐MA 2006, identical at both sites 2011–2017 after the other site adopted R‐Hyper‐CVAD/R‐MA 2011, and excellent 2018–2020 when R‐Hyper‐CVAD/R‐MA use increased to 75% of patients. Despite considerable toxicity, also patients aged 61–69 years showed better survival with R‐Hyper‐CVAD/R‐MA. This is the largest single‐centre series of patients treated with R‐Hyper‐CVAD/R‐MA, showing favourable outcome in high‐risk aggressive B‐cell lymphoma.